2016
DOI: 10.3892/mmr.2016.5222
|View full text |Cite
|
Sign up to set email alerts
|

Resolution acute respiratory distress syndrome through reversing the imbalance of Treg/Th17 by targeting the cAMP signaling pathway

Abstract: Acute respiratory distress syndrome (ARDS) is a severe cause of respiratory failure with a mortality rate as high as 40‑46% and without any effective pharmacological treatment available. The present study provided a novel strategy for the treatment of ARDS by specifically interfering with cyclic adenosine monophosphate (cAMP) signaling. Pre-treatment with the phosphodiesterase antagonist pentoxifyllinum (PTX) obviously attenuated lung injury and reduced the mortality of mice with cecal ligature and puncture (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 22 publications
0
25
0
Order By: Relevance
“…Therefore, regulation of CD4 + CD25 + Foxp3 + Tregs and Th17 cells may promote the recovery of ALI/ARDS. A murine study has found that reversal of the imbalance of Treg/Th17 by targeting the cAMP signalling pathway promoted resolution of ARDS …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, regulation of CD4 + CD25 + Foxp3 + Tregs and Th17 cells may promote the recovery of ALI/ARDS. A murine study has found that reversal of the imbalance of Treg/Th17 by targeting the cAMP signalling pathway promoted resolution of ARDS …”
Section: Introductionmentioning
confidence: 99%
“…A murine study has found that reversal of the imbalance of Treg/Th17 by targeting the cAMP signalling pathway promoted resolution of ARDS. 9 The objective of our study was to investigate if recovery from lung injury can be promoted by the modulation of CD4 + CD25 + Foxp3 + Tregs and Th17 cells. In the wellestablished model of intratracheal lipopolysaccharide (LPS)-induced lung injury, we modulated Treg numbers by CD25 depletion and TGF-β neutralization, and Th17 cell abundance by IL-17A and IL-22 neutralization.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that speci c regulation of T cell differentiation could improve the immunity and in ammation state of ARDS in animal models, resulting in prognosis improvement 21,23,24 . It was also found in our study that the regulation of T cell differentiation in patients with community-acquired pneumonia was directly related to their prognosis 25 .…”
Section: Discussionmentioning
confidence: 99%
“…8). Several studies have veri ed that Treg/Th17 skewing plays a crucial role in ARDS (7,8,10,25,26). LPS, an endotoxin originating from the cell wall of gram-negative bacteria, was most used for a bacterial hyperin ammatory model of experimental ARDS (27).…”
Section: Effects Of Mir-155 Expression On Proliferation Capacity and mentioning
confidence: 99%
“…Excessive generation and activation of Th17 cells attribute to hyperin ammatory damage (9). Recent clinical studies among ARDS patients have identi ed a signi cantly closed link between increased Th17 frequency and greater illness severity and showed the levels of IL-17A were increased in bronchoalveolar lavage (10). Accordingly, Tregs, characterized by forkhead box P3(Foxp3) contribute to the resolution of hyperin ammatory response by regulating responses mediated by T helper cells.…”
mentioning
confidence: 99%